Aromatase (CYP19) promoter gene polymorphism and risk of non-viral hepatitis-related hepatocellular carcinoma - Koh, Woon-Puay (2011)
BACKGROUND: Experimental studies suggest that sex hormones may induce or promote the development of hepatocellular carcinoma (HCC). Androgens are converted to estrogens by the CYP19 gene product, aromatase. Hepatic aromatase level and activity have been shown to be markedly elevated in HCC. Aromatase expression in liver tumors is driven by a promoter upstream of CYP19 exon I.6. METHOD: We first identified an A/C polymorphism in the exon I.6 promoter of the CYP19 gene. To determine whether allelic variants in the CYP19 I.6 promoter differ in their ability to drive gene expression, we carried out an in-vitro reporter gene assay. We then studied the association between this polymorphism and HCC risk in two complementary case-control studies: one in high-risk southern Guangxi, China, and another in low-risk US non-Asians of Los Angeles County. RESULTS: Transcriptional activity was 60% higher for promoter vectors carrying the rs10459592 C allele compared to those carrying an A allele (p=0.007). In both study populations, among subjects negative for at-risk serologic markers of hepatitis B or C, there was a dose-dependent association between number of high activity C allele and risk of HCC (p for trend=0.014). Risk of HCC was significantly higher [odds ratio (OR) = 2.25, 95% confidence interval (CI) = 1.18–4.31] in subjects homozygous for the C allele compared to those homozygous for the A allele. CONCLUSION: Our study provides epidemiologic evidence for the role of hepatic aromatization of androgen into estrogen in the development of non-viral hepatitis-related HCC.